2017
DOI: 10.1680/jsuin.17.00053
|View full text |Cite
|
Sign up to set email alerts
|

Zn-Mg and Zn-Ag Degradation Mechanism Under Biologically Relevant Conditions

Abstract: Zinc (Zn) alloys form a promising new class of biodegradable metals that combine suitable mechanical properties with the favorable degradation properties of pure zinc. However, the current understanding of the influence of alloying elements on the corrosion of zinc alloys, in biologically relevant media, is limited. The authors studied the degradation of three alloys, zinc-4 wt% silver (Ag), zinc-0·5 wt% magnesium (Mg) and zinc-3 wt% magnesium by in situ electrochemical impedance spectroscopy (EIS). After expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
2
18
1
Order By: Relevance
“…This result is consistent with that reported by Punith et al [42], who studied the corrosion of Zn/Ag composites in NaCl saline solutions and associated the lower corrosion rate of Zn/Ag composites with respect to Zn because the Ag particles occluded in the coating minimize defects in the coating, which are active sites for corrosion. However, the trend of our results is contrary to those reported by Sikova-Jasenska et al [18], who found that by increasing the Ag content in Zn-Ag alloys formed by smelting at 650 • C, the values of j corr and CR were slightly increased when using Hank's solution as electrolyte, and those of Törne et al [17], who reported increases in the corrosion rate of Zn-4Ag alloys (4 wt.% Ag) (formed by smelting at 550 • C) with respect to pure Zn. The observed differences can be explained taking into account that in the Zn-Ag alloy obtained by heat treatment the formation of intermetallic compounds as AgZn 3 of low corrosion resistance is favoured, contrary to what happens with Zn/AgP composite electrodeposited coatings in which these types of compounds are not formed.…”
Section: Polarization Curvescontrasting
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with that reported by Punith et al [42], who studied the corrosion of Zn/Ag composites in NaCl saline solutions and associated the lower corrosion rate of Zn/Ag composites with respect to Zn because the Ag particles occluded in the coating minimize defects in the coating, which are active sites for corrosion. However, the trend of our results is contrary to those reported by Sikova-Jasenska et al [18], who found that by increasing the Ag content in Zn-Ag alloys formed by smelting at 650 • C, the values of j corr and CR were slightly increased when using Hank's solution as electrolyte, and those of Törne et al [17], who reported increases in the corrosion rate of Zn-4Ag alloys (4 wt.% Ag) (formed by smelting at 550 • C) with respect to pure Zn. The observed differences can be explained taking into account that in the Zn-Ag alloy obtained by heat treatment the formation of intermetallic compounds as AgZn 3 of low corrosion resistance is favoured, contrary to what happens with Zn/AgP composite electrodeposited coatings in which these types of compounds are not formed.…”
Section: Polarization Curvescontrasting
confidence: 99%
“…In this sense, Niu et al [16] proposed a Zn-Cu alloy as a biodegradable material for application in vascular stents. Törne et al [17] studied the degradation mechanism of Zn-Mg and Zn-Ag alloys obtained by smelting at 550 • C, immersed in Ringer's solutions. The microgalvanic corrosion of the Zn-Ag alloy causes the accumulation of the AgZn 3 phase on the surface, and this accumulation could cause complications in the regeneration of the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, AgZn 3 particles act as sites for disruption of any oxide/hydroxide film covering the Zn-Ag alloys’ surfaces. Recently, Torne et al [90] carried out an investigation on the degradation mechanism of as-cast Zn-4.0Ag alloy in a Ringer’s solution. Microstructural characterization on samples after 30 days of immersion showed selective corrosion surrounding AgZn 3 dendrites, leaving the AgZn 3 phase at the implant surface; nevertheless, no evident sign of corrosion pits was observed.…”
Section: Zinc Alloy Candidates For Stenting Applicationsmentioning
confidence: 99%
“…It was speculated that Mg 2 Zn 11 particles promote a more aggressive activity of macrophages in an attempt to metabolize this alloy phase known for increased corrosion resistance. An enrichment of intermetallic particles in the corrosion product layer during in vivo degradation of zinc alloys and their effect on tissue regeneration is of concern [90] and has not been addressed yet.…”
Section: Zinc Alloy Candidates For Stenting Applicationsmentioning
confidence: 99%
“…Moreover, their morphology, chemical composition and dimension severely affect the corrosion processes. Apart from oxidation, atmospheric sulfidation process also occur via reacting with reduced sulfur ligands, forming a silver sulfide corrosion layer . However, S‐containing species are rare (H 2 S 0.3 ppb, COS 0.6 ppb) in air, which are much lower than the oxidation content (around 20.95%) .…”
Section: Oxidation Mechanism and Antioxidation Strategiesmentioning
confidence: 99%